2011
DOI: 10.1007/s10888-011-9191-2
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the effect of spell recurrence on poverty dynamics—evidence from Spain

Abstract: Accounting for the time individuals spend below the poverty line is an important dimension in order to design social policies to fight against poverty. The literature is currently aiming to construct a consistent aggregate measure of poverty over time that takes into account individual income lifetime profiles. It is however, far from clear which aspects of the specific patterns of poverty spells should be included. Using longitudinal data for Spain, this paper shows that the effect of spell recurrence on pove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 31 publications
1
32
0
3
Order By: Relevance
“…Moreover, as Jenkins (2011) explains: "Markovian models assume that the accumulated impact of a person's history of poverty (and non-poverty) is expressed entirely by last year's poverty status" (Jenkins 2011, p. 332). As already mentioned, Arranz and Cantó (2011), to cite the most recent study of the Spanish case, have shown the importance of duration in poverty dynamics analyses (see also Devicienti and Gualtieri 2007). However, Devicienti (2001) also finds that controlling for unobserved characteristics reduces the importance of duration dependence.…”
Section: The Modelmentioning
confidence: 95%
See 4 more Smart Citations
“…Moreover, as Jenkins (2011) explains: "Markovian models assume that the accumulated impact of a person's history of poverty (and non-poverty) is expressed entirely by last year's poverty status" (Jenkins 2011, p. 332). As already mentioned, Arranz and Cantó (2011), to cite the most recent study of the Spanish case, have shown the importance of duration in poverty dynamics analyses (see also Devicienti and Gualtieri 2007). However, Devicienti (2001) also finds that controlling for unobserved characteristics reduces the importance of duration dependence.…”
Section: The Modelmentioning
confidence: 95%
“…As can be observed, entry rates fluctuate between 6.17 and 8.18 % while exit rates do so between 31.09 and 41.15 %. However, as similarly pointed out by Arranz and Cantó (2007), there is no clear trend of poverty outflows and inflows throughout the period and it is difficult to distinguish, on a descriptive level, a different sample retention process for those who are poor and not poor at t − 1. 8 Finally, Table 4 presents household income level as a percentage of the median of those individuals entering or escaping poverty, which enables assessment of the income level that is the starting point for a transition.…”
Section: Poverty Dynamics In Spain: a Descriptionmentioning
confidence: 95%
See 3 more Smart Citations